Teaching and learning elementary social studies - Ellis, Arthur K. (Pearson, 2010)
"With a wealth of lesson plans and practical guidance, this perennial best-seller provides instructional strategies for involving K-8 children in social studies content that emphasize concepts, inquiry, and moral development."--Publisher's description.